Experimental and Theoretical Evidence for Increased Ganglion Dynamics During Fractional Flow in Mixed‐Wet Porous Media. Issue 5 (8th May 2018) - Zou, Shuangmei; Armstrong, Ryan T.; Arns, Ji‐Youn; Arns, Christoph H.; Hussain, Furqan
Abstract: X‐ray microtomography (micro‐CT) provides a nondestructive way for estimating rock properties such as relative permeability. Relative permeability is computed on the fluid distributions generated on three dimensional images of the pore structure of a rock. However, it is difficult to numerically reproduce actual fluid distributions at the pore scale, particularly for a mixed‐wet rock. Recent advances in imaging technologies have made it possible to directly resolve a large field of view for arbitrary wetting conditions. Herein, the objective of this study is to evaluate relative permeability computations on imaged fluid distributions under water‐wet and mixed‐wet conditions. By simultaneously injecting oil and brine on a Bentheimer sandstone before and after wettability alteration, imaged fluid distributions are obtained under steady state conditions. Then relative permeability computations performed on imaged fluid distribution are compared with experimental data obtained on the same rock. We find that relative permeabilities computed directly from imaged fluid distributions show agreement with experimental data in water‐wet rock while for mixed‐wet rock, the imaged connected pathways provided a poor estimate of relative permeability. Analysis of imaged fluid distributions and connectivity demonstrates that under mixed‐wet conditions, increased dynamic connectivity and ganglion dynamics result in non‐equilibrium effects at the fluid‐fluid interface. These effects result in more energy dissipation during fractional flow in mixed‐wet systems and thus lower effective permeability than water‐wet rock at the same saturation. Key Points: Nonwetting phase is less connected under mixed‐wet than water‐wet conditions Dynamic connectivity is observed more frequently under mixed‐wet conditions Energy balance demonstrates higher propensity for interface creation under mixed‐wet conditions